Placenta Accreta Spectrum in delivered women is associated with history of curettage: A case-control study at Dr. Moewardi General Hospital, Surakarta, Indonesia - Helena Adelia Prabowo; Nutria Widya Purna Anggraini; Asih Anggraeni; Sigit Setyawan (Majalah Obstetri dan Ginekologi)
HIGHLIGHTS